UTILIZATION OF CHITOSAN FROM FRESHWATER CRAYFISH (Cherax quadricarinatus) CARAPACE WASTE TO MAKING LIP BALM - Paradise, Nadia; Sukmiwati, Mery; Edison, Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This study was aimed to determine the characteristics of chitosan from freshwater crayfish carapace (Cherax quadricarinatus), to determine the effect of adding chitosan with different concentrations on the quality of lip balm and to determine the addition of the best chitosan concentration on lip balm. The method used in this research was an experimental method on the effect of adding chitosan from freshwater crayfish (Cherax quadricarinatus) carapace to making lip balm. Tests used in this study were the yield, moisture, ash content, nitrogen content, and the degree of deacetylation in the determination of chitosan quality and pH test, emulsion stability test and humectant test in the determination of lip balm quality. Based on the results showed that the characteristics of chitosan had a yield valueof 20.38%, 7.35% moisture content, 4.34% ash content, 4.54% nitrogen content and 73.74% deacethylation degree.The addition of chitosan with different concentrations in lip balm had a significant effect on pH value, emulsion stability and humectant of lip balm. The best treatment is A3(the addition of 3% chitosan concentration) based on the pH value of 5.50; 99.46% emulsion stability; and humectant of 95.14%. Keywords:chitosan, freshwater crayfish, lip balm.